2018
DOI: 10.5603/fm.a2018.0012
|View full text |Cite
|
Sign up to set email alerts
|

Sonography in the instability of the long head of the biceps tendon confronted with histopathologic and arthroscopic findings

Abstract: Background: Disorders of the long head of the biceps (LHB) tendon are a common (Folia Morphol 2018; 77, 3: 583-590)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The authors of included studies used mostly the four-variable classical Bonar score [ 19 , 20 , 23 , 24 , 25 , 26 , 29 , 31 , 32 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of included studies used mostly the four-variable classical Bonar score [ 19 , 20 , 23 , 24 , 25 , 26 , 29 , 31 , 32 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…None of the included sonographic modality studies presented a clear radiological association with histopathology. Authors of the sonographic study of the LHBT showed abundant histopathological alterations and concomitant sonographic changes, such as hypoechogenicity and increased tendon diameter, however, no statistically significant correlation was found [ 25 ]. Cook et al suggested that imaging abnormalities such as hypoechogenicity requires a high accumulation of the ground substance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound achieved success in dynamic assessment of LHBT, but not that of BRP integrity and detection of concomitant intra-articular pathologies, which required further arthroscopic investigation. 12,13 Dynamic arthroscopic examination of the pulley structures is a useful tool for early detection of symptoms that may progress to ASI, such as BRP lesions including partial tear and SGHL insufficiency. 3…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography (US) is a reliable imaging method to evaluate soft tissue structures, such as muscles, tendons, aponeurosis, and ligaments. For tendinopathy, US reveals structural abnormalities, such as tendon thickening, textural heterogeneity with intra-tendinous focal hypoechoic areas, and altered vascularity [ 5 ]. There is a consensus on the role of US measurement of the thickness of the plantar fascia in establishing the diagnosis of plantar fasciitis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%